The effects of ZnO nanoparticles on male germ cells - Pinho, Ana Rita Arede (2019)
Nowadays, a new concept of nanotechnology, “the nanomedicine” has been developed. Certain nanoparticles offer an exceptional set of characteristics that improve the diagnosis and treatment quality and efficacy on medicine. Zinc Oxide Nanoparticles (ZnO NPs) are a type of metal oxide nanoparticles with an extensive use, for example, in drug delivery systems, bioimaging and cancer therapy. Several authors have focused on biosafety studies of ZnO NPs, as their size and surface area favour the entrance and accumulation in organism, which can induce toxic effects. ZnO NPs have been identified, as a dose and time dependent cytotoxic inducer in testis and in some male germ cells, like spermatozoa and spermatocyte. In this way, it is important to understand the consequences of ZnO NPs exposure on the first cell stage of spermatogenesis, the spermatogonia. Thus, the aim of this work was to evaluate the effects of ZnO NPs on spermatogonia. GC-1 spg cell line derived from spermatogonia of mouse testes was treated with different concentrations of ZnO NPs, namely 0, 1, 5, 8, 10 and 20 μg/ml for 6 hours and 12 hours. The study was divided into two stages. Firstly, cytotoxicity resulting from exposure to ZnO NPs was evaluated through cell viability assays, intracellular ROS detection, progression of apoptosis/necrosis analysis and levels of DNA damage. At the end, cytoskeleton protein levels (acetylated α-tubulin, β-tubulin, β-actin and F-actin) and the nuclear intern protein Sun1 were assessed. According with results, higher concentrations of ZnO NPs have a toxic effect in GC-1: viability decreased, ROS intracellular levels production, DNA damage and cell death ratio increase. Further, at cytoskeleton and nucleoskeleton level, significant changes were verified. In conclusion, ZnO NPs induce cytotoxic effects on GC-1 cells in a time and dose-dependent manner. Short time exposure and low concentration of zinc oxide nanoparticles do not induce cytotoxicity on spermatogonia.